UTILIZATION OF HERBAL POWDER TO INCREASE THE ECONOMY IN NURUL HUDA ISLAMIC BOARDING SCHOOL, SIDOARJO - Setiawati, Yuani; kurnijasanti, rochmah; Sudjarwo, Sri Agus; Fitriati, Mariza (Universitas Airlangga, 2024)
In the context of global economic contestation, the presence of an independent Islamic boarding school economic community will become social capital and inspiration for the community so that the local community's economy is not defeated and displaced by global players. The Nurul Huda Islamic boarding school is included in the category of Islamic boarding schools that do not yet have a business unit, even though the Nurul Huda Islamic boarding school has vacant land that can be utilized by students by managing herbal plants. Implementation of the community service program is carried out through several activities: 1) Providing material about various kinds of herbs and their benefits 2) Demonstration and practice of formulating and making various kinds of herbal powders 3) Demonstration and practice of formulating and making various kinds of herbal drinks 4) Demonstration and practice of formulation and making herbal granules 5) Demonstration, practice of formulation and making herbal effervescent powder 6) Packing and labelling practices for marketing 7) Making a website for product marketing. This community service produces output in the form of: 1) Publication in the Sinta 4 journal, namely the Abdinus journal / Journal of Indonesian Service 2) Publication on online news media. The results of implementing this activity were able to increase the knowledge and skills of students at Nurul Huda Islamic boarding school.